2017
DOI: 10.3390/genes9010002
|View full text |Cite
|
Sign up to set email alerts
|

Differential Preference of Burkholderia and Mesorhizobium to pH and Soil Types in the Core Cape Subregion, South Africa

Abstract: Over 760 legume species occur in the ecologically-heterogeneous Core Cape Subregion (CCR) of South Africa. This study tested whether the main symbionts of CCR legumes (Burkholderia and Mesorhizobium) are phylogenetically structured by altitude, pH and soil types. Rhizobial strains were isolated from field nodules of diverse CCR legumes and sequenced for 16S ribosomic RNA (rRNA), recombinase A (recA) and N-acyltransferase (nodA). Phylogenetic analyses were performed using Bayesian and maximum likelihood techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 85 publications
1
11
0
Order By: Relevance
“… Paraburkholderia are commonly misidentified as Burkholderia or indeterminately categorized as part of the ‘ Burkholderia-Caballeronia-Paraburkholderia ’ group [80]. Several studies of lignin or litter degradation and root- or fungi-associated bacteria report major trends in ‘ Burkholderia ’, but retrospective analysis reveals that these bacteria were actually Paraburkholderia and, to a lesser extent, Caballeronia (Table S5) [57, 81–90]. The problem of taxonomic misidentification is compounded by the poor phylogenetic resolution of 16S rRNA gene-based classifications for Paraburkholderia .…”
Section: Discussionmentioning
confidence: 99%
“… Paraburkholderia are commonly misidentified as Burkholderia or indeterminately categorized as part of the ‘ Burkholderia-Caballeronia-Paraburkholderia ’ group [80]. Several studies of lignin or litter degradation and root- or fungi-associated bacteria report major trends in ‘ Burkholderia ’, but retrospective analysis reveals that these bacteria were actually Paraburkholderia and, to a lesser extent, Caballeronia (Table S5) [57, 81–90]. The problem of taxonomic misidentification is compounded by the poor phylogenetic resolution of 16S rRNA gene-based classifications for Paraburkholderia .…”
Section: Discussionmentioning
confidence: 99%
“…nutrient or water availability) often explain some variability in root nodule community structure (Vuong et al, 2017), the host plant is normally the strongest filter to rhizobial propagation during their endophytic life stage (Denison and Kiers, 2011). Indeed, legume composition in the Core Cape Region is known to be strongly driven by edaphic factors (Dludlu et al, 2017), suggesting the effects of edaphic factors on root nodule communities are most likely mediated by plant hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Its seeds germinate under elevated soil fertility during postfire successions, transitioning towards severely nutrient-poor conditions over its life span (Maistry et al, 2015). Second, the species contains distinct ecotypes in the wild (Hawkins et al, 2011), often sympatric with plantations and in a highly heterogeneous landscape where physical barriers to dispersal are common (Cowling et al, 2009;Dludlu et al, 2017). Lastly, recent studies have found rooibos to associate with a wide diversity of rhizobia (Hassen et al, 2012;Le Roux et al, 2017;Ramoneda et al, 2020), particularly at the seedling stage.…”
Section: Introductionmentioning
confidence: 99%
“…This is a relatively new genus to be described by legume microbiologists (Moulin et al 2001), and little is known of its ecology (Sprent et al 2017). There are indications that Burkholderia, particularly those from the Fynbos, favour acidic soils (Dludlu et al 2017). Knowing that the introduction of Fynbos legumes to Australia has hitherto been compromised by the poor competitive ability of their symbionts (Gerding et al 2012(Gerding et al , 2013(Gerding et al , 2014, experiments are underway to select strains of Burkholderia suitable for L. ambigua that are well adapted to the edaphic stresses of the target soils in WA.…”
Section: Further Questions To Be Answeredmentioning
confidence: 99%